2018
DOI: 10.2196/jmir.8338
|View full text |Cite
|
Sign up to set email alerts
|

A Perioperative eHealth Program to Enhance Postoperative Recovery After Abdominal Surgery: Process Evaluation of a Randomized Controlled Trial

Abstract: BackgroundElectronic health (eHealth) interventions have proven effective, but implementation in clinical practice is difficult. More research focusing on the implementation process of eHealth interventions is necessary.ObjectiveThe objective of this study was to describe the process evaluation of a perioperative eHealth intervention, aiming to enhance recovery after laparoscopic abdominal surgery.MethodsA process evaluation was carried out alongside a multicenter randomized controlled trial. Patients aged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Of the 6525 participants who have completed the prescreening survey, 5337 (81.54%) consented to participate in the registry and agreed to be contacted at a later date for future center studies. The majority of participants enrolled reported hearing about the center via digital recruitment strategies (eg, Instagram, Reddit) and research registries (eg, ResearchMatch) [ 17 ]. Of the 14,557 records in the referral tracking database, 770 (5.29%) have been enrolled in a clinical trial.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 6525 participants who have completed the prescreening survey, 5337 (81.54%) consented to participate in the registry and agreed to be contacted at a later date for future center studies. The majority of participants enrolled reported hearing about the center via digital recruitment strategies (eg, Instagram, Reddit) and research registries (eg, ResearchMatch) [ 17 ]. Of the 14,557 records in the referral tracking database, 770 (5.29%) have been enrolled in a clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…Other advantages include the ability to balance recruiter caseloads using features that support monitoring and assignment or reassignment of cases to other staff. The capture of objective data pertaining to study eligibility at each stage of the recruitment pipeline allowed for ongoing adjustments and optimization of recruitment strategies to improve efficiency and cost-effectiveness (see Lattie et al [ 17 ] for a more detailed description). In addition to staff-facing advantages, participant-facing advantages include the ability to take the survey from a browser or mobile device at any time and it is an easy way to send contact information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a recent systematic review of barriers and facilitators to implementation included 47 studies and identified factors such as patient and professional acceptance of e-mental health and fit with existing technologies [ 44 ]. In addition, while implementation of e-health interventions more generally is well covered in existing research [ 45 - 51 ], there have been recent calls to place more focus on implementation of e-health [ 52 ] to enable health care organizations to benefit from the promises of e-health solutions [ 53 ].…”
Section: Introductionmentioning
confidence: 99%